2011
DOI: 10.1177/1359105311405350
|View full text |Cite
|
Sign up to set email alerts
|

Non-conventional practices and immune functioning among individuals receiving conventional care for HIV

Abstract: Objective to examine the relationships among non-conventional practices, adherence and immune functioning in individuals with HIV. Methods 92 participants completed an interview on non-conventional practices (complementary and alternative medicines (CAM), psychosocial therapies, and religious practice). They also completed the Psychiatric Symptom Index and the AIDS Clinical Trials Group Adherence Follow-up Questionnaire. Medical chart reviews determined CD4 count and viral load. Results Hierarchical logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Evangelicals also had a greater chance of inadequate adherence to ART. However, studies have shown that religion is associated with positive health behaviors (28) , better adherence to ART, quality of life and social support (28)(29)(30) . In a study conducted in Africa, some participants reported that certain religions encouraged the abandonment of ART, believing in healing through prayer (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Evangelicals also had a greater chance of inadequate adherence to ART. However, studies have shown that religion is associated with positive health behaviors (28) , better adherence to ART, quality of life and social support (28)(29)(30) . In a study conducted in Africa, some participants reported that certain religions encouraged the abandonment of ART, believing in healing through prayer (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Religion has been found to be associated with positive health outcomes and behaviors such as HIV medication adherence [40], quality of life, social support, effective coping strategies and less psychological distress [41]. Positive health effects for persons living with HIV, in general, have been linked to spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…Ten were north American, 67,69,[71][72][73][74][77][78][79]81 four from Australia, 10,70,76,80 and one from Switzerland. 75 One of the key reasons for using CAM was to provide a method to self-manage health or to give a sense of control, 10,71,77,80 to cope with uncertainty, 71 manage symptoms, 71 give freedom from and additional choice to medical regimens, 10,71,76,80 and attempt to normalize health status, maintain health, or find wellness.…”
Section: Attitudes To Cam Reasons For Use and Decision-makingmentioning
confidence: 99%